2020
DOI: 10.1093/femspd/ftaa075
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus matrix protein targets host actin cytoskeleton: a protein–protein interaction analysis

Abstract: Multifunctional matrix protein (M) of rabies virus (RABV) plays essential roles in the pathogenesis of rabies infection. Identification of M protein interacting partners in target hosts could help to elucidate the biological pathways and molecular mechanisms involved in the pathogenesis of this virus. In this study, two-dimensional Far-western blotting (2D-Far-WB) technique was applied to find possible matrix protein partners in the rat brainstem. Recombinant RABV M was expressed in Pichia pastoris and was par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Two-dimensional far-western blotting confirmed that the M protein of RABV also interacts with six different proteins in rat brain stem including the actin cytoplasmic-1 that was verified in co-immunoprecipitation. All these proteins regulate vital cellular processes as described earlier and the findings were also verified in mouse neuro-N2a cells ( 60 ).…”
Section: Resultssupporting
confidence: 66%
“…Two-dimensional far-western blotting confirmed that the M protein of RABV also interacts with six different proteins in rat brain stem including the actin cytoplasmic-1 that was verified in co-immunoprecipitation. All these proteins regulate vital cellular processes as described earlier and the findings were also verified in mouse neuro-N2a cells ( 60 ).…”
Section: Resultssupporting
confidence: 66%
“…First, the internalization and uptake of RABV requires an intact actin network, and the depolymerization of actin filaments inhibits the virus infection. Next, RABV utilizes the microtubules and the motor protein dynein/kinesin for intracellular transport [ 18 , 19 , 20 , 29 , 30 ]. During this stage, the M protein enhances the expression of cellular histone deacetylase 6 (HDAC6) to depolymerize the microtubules and facilitate viral RNA synthesis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the major structural components of IFs in skeletal, cardiac, and some smooth muscle cells, desmin is important for the maintenance and integrity of the cytoskeleton [ 17 ]. Our identification of desmin as a novel host interactor with RABV-M is particularly intriguing since RABV exploits the cytoskeleton network to facilitate different stages of its lifecycle and the development of pathological processes [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have also found that the actin filament system provides the driving force required for viral assembly, budding, and release after infection, thereby participating in the regulation of the viral life cycle [2]. Clinically, studies have demonstrated the important role of the actin filament system in viral infection-related diseases [5][6][7].…”
Section: Actin Filamentsmentioning
confidence: 99%